Neonatal AAV gene therapy rescues hearing in a mouse model of SYNE4 deafness - Taiber, Shahar (EMBO Mol Med, 2020)
Genetic variants account for approximately half the cases of congenital and early‐onset deafness. Methods and technologies for viral delivery of genes into the inner ear have evolved over the past decade to render gene therapy a viable and attractive approach for treatment. Variants in SYNE4, encoding the protein nesprin‐4, a member of the linker of nucleoskeleton and cytoskeleton (LINC), lead to DFNB76 human deafness. Syne4 (−/−) mice have severe‐to‐profound progressive hearing loss and exhibit mislocalization of hair cell nuclei and hair cell degeneration. We used AAV9‐PHP.B, a recently developed synthetic adeno‐associated virus, to deliver the coding sequence of Syne4 into the inner ears of neonatal Syne4 (−/−) mice. Here we report rescue of hair cell morphology and survival, nearly complete recovery of auditory function, and restoration of auditory‐associated behaviors, without observed adverse effects. Uncertainties remain regarding the durability of the treatment and the time window for intervention in humans, but our results suggest that gene therapy has the potential to prevent hearing loss in humans with SYNE4 mutations.